1971
DOI: 10.1002/pen.760110205
|View full text |Cite
|
Sign up to set email alerts
|

Cold forming of plastics part I. Draw forming of thermoplastic sheets

Abstract: An experimental procedure is outlined to examine the potential of thermoplastic sheets in draw forming. Experiments carried out on a variety of materials indicate that the following requirements must be fulfilled for a thermoplastic sheet to be cold formable: (1) The glass transition of polymer should be above ambient temperature and above the temperature of forming, (2) tensile elongation at break should equal or exceed 30%, (3) ratio of tensile to compressive yield stress should equal or exceed 1.6 and (4) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
(1 reference statement)
2
6
0
Order By: Relevance
“…Once a polymer has been cold formed, Johnson has shown that the deformation of unmelted particles can lead to the development of nonuniform microstructures, which may result in parts with high residual stress, reduced mechanical properties and fatigue . In fact, Li et al have described that cold formed polymers have a lower heat distortion temperature than their thermoformed counterparts, where cold formed components readily deform below their T g due to the high amount of residual stresses induced by the deformation process .…”
Section: Introductionsupporting
confidence: 91%
See 4 more Smart Citations
“…Once a polymer has been cold formed, Johnson has shown that the deformation of unmelted particles can lead to the development of nonuniform microstructures, which may result in parts with high residual stress, reduced mechanical properties and fatigue . In fact, Li et al have described that cold formed polymers have a lower heat distortion temperature than their thermoformed counterparts, where cold formed components readily deform below their T g due to the high amount of residual stresses induced by the deformation process .…”
Section: Introductionsupporting
confidence: 91%
“…With respect to crystallinity, Martins et al observed that high crystallinity is counterproductive due to the resulting high stiffness and limited ductility, while low and medium crystallinities offer low spring back and high ductility, respectively . In terms of processability of the polymers before and after deformation phenomena, Li et al argue that the processability of brittle polymers considered not formable can be improved by performing a preorientation by means of cold rolling, which improves their formability . Once a polymer has been cold formed, Johnson has shown that the deformation of unmelted particles can lead to the development of nonuniform microstructures, which may result in parts with high residual stress, reduced mechanical properties and fatigue .…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations